Integration of Interactive Video in Problem-Based Learning on Environmental Change and Conservation Material to Enhance Students’ Critical Thinking Skills at SMA Negeri 2 Indramayu - Lissa; Nur Subkhi; Iqbal Firmansyah (Kilau Publishing, 2026)
This study aimed to determine the effect of integrating interactive video in problem-based learning (PBL) on students’ critical thinking skills in the topic of environmental change and conservation. The research was conducted at SMA Negeri 2 Indramayu during the 2024/2025 academic year using a quasi-experimental design with a non-equivalent control group. Data were collected through a critical thinking test consisting of validated essay questions. The analysis included normality, homogeneity, and independent sample t-tests. The results showed that students taught using PBL integrated with interactive videos achieved higher critical thinking skills than those taught conventionally. The integration of interactive videos improved students’ understanding, curiosity, and analytical ability toward environmental issues. Therefore, this approach can effectively foster critical thinking skills in biology learning.